2017
DOI: 10.1111/scs.12455
|View full text |Cite
|
Sign up to set email alerts
|

Women with vulvodynia: awareness and knowledge of its care among student healthcare staff

Abstract: The student healthcare staff who meet and care for women of fertile age have irregular awareness and knowledge of vulvodynia and its care. The creation of educational programs to develop such awareness and knowledge is recommended to obtain a standard quality of care for all women with vulvodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Prior to the actual study with student healthcare providers, the instrument was modified and clarified on the basis of the pilot study. At baseline (Törnävä et al, 2017) and in the follow-up survey, all four subscales in Part 1 showed acceptable internal consistency (Table 2).…”
Section: Survey Instrumentmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior to the actual study with student healthcare providers, the instrument was modified and clarified on the basis of the pilot study. At baseline (Törnävä et al, 2017) and in the follow-up survey, all four subscales in Part 1 showed acceptable internal consistency (Table 2).…”
Section: Survey Instrumentmentioning
confidence: 99%
“…2005;Toeima and Nieto. 2011;Phillips et al, 2013); only one study also assessed the perspectives of nursing and therapy staff (Törnävä et al, 2017). The studies that investigated women's experiences of the care they received reported that the knowledge of healthcare staff was inadequate from the patients' perspective (Gordon et al, 2003;Buchan et al, 2007;Törnävä et al, 2012).…”
Section: Knowledge Of Vulvodynia and Its Carementioning
confidence: 99%
See 3 more Smart Citations